APOE genotype alters the lipid droplet proteome and modulates droplet dynamics. (20th December 2022) - Smith, Cathryn T; Friday, Cassi; Devanney, Nicholas; Allenger, Elizabeth J.; Cornea, Ana Maria L/K; Gordon, Scott; Johnson, Lance A
Abstract: Background: The microglial immune response is a significant contributor to Alzheimer's disease (AD) pathophysiology and neurodegeneration. Aging microglia accumulate lipid droplets (LDs), have high levels of reactive oxygen species, secrete pro‐inflammatory cytokines, and are defective in phagocytosis. The E4 allele of Apolipoprotein E ( APOE ) is the strongest genetic risk factor for late‐onset AD, and is associated with heightened neuroinflammation and increased LD formation. We hypothesize E4 microglia have increased LD formation under basal conditions and a higher capacity to form LDs under stress, resulting in greater pro‐inflammatory cytokine production. We characterized LD development in microglia in the context of APOE genotype and analyzed LD surface proteins and lipid content from control and lipopolysaccharide (LPS) stimulated ApoE3 and ApoE4 mice. Method: Primary microglia were isolated from mice expressing human ApoE3 and ApoE4. Microglia were exposed to 250uM oleic acid (OA), 10ug/mL LPS, OA+LPS, dead N2A cells, or dead N2As+LPS. ApoE3 and ApoE4 expressing mice were injected with saline (control) or LPS (5mg/kg) and perfused at 24h. Livers were extracted, the LD enriched supernatant fraction was collected after centrifugation, and proteomic and lipidomic analyses were performed. Result: Primary microglia from ApoE4 mice accumulated more LDs at baseline, with exogenous OA, LPS stimulation, and N2As as a percentage of E3 control across multiple experiments (E3 v E4 p‐values: baseline, 0.0317; LPS, 0.0032; OA, 0.0277; N2A, 0.0192). Western blots on LD fractions confirm LD enrichment by surface protein, PLIN2, along with increased expression of PLIN2 (i.e. more LDs) in E4 LPS mice. Proteomics reveal LD fractions from E4 mice are enriched for proteins involved in innate immunity, while E3 LDs are enriched for proteins involved in lipid b‐oxidation. Conclusion: E4 microglia accumulate more LDs compared to E3 microglia under all conditions tested. The proteomic profile of E4 liver LDs support the hypothesis that E4 expression increases inflammation under basal conditions, and upon stimulation, causes a more robust response. Increased LD formation is present in non‐aged, non‐diseased E4 cells, suggesting preclinical dysfunction associated with the highest risk APOE genotype. A better understanding of LD dynamics within these cells and their functional implications can provide targets to improve E4‐related outcomes.